2023
DOI: 10.1126/sciimmunol.add1823
|View full text |Cite
|
Sign up to set email alerts
|

IL-21R signal reprogramming cooperates with CD40 and BCR signals to select and differentiate germinal center B cells

Abstract: Both B cell receptor (BCR) and CD40 signaling are rewired in germinal center (GC) B cells (GCBCs) to synergistically induce c-MYC and phosphorylated S6 ribosomal protein (p-S6), markers of positive selection. How interleukin-21 (IL-21), a key T follicular helper (T FH )–derived cytokine, affects GCBCs is unclear. Like BCR and CD40 signals, IL-21 receptor (IL-21R) plus CD40 signals also synergize to induce c-MYC and p-S6 in GCBCs. However, IL-21R plus CD40 stimulation differentially affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 70 publications
(144 reference statements)
7
14
0
Order By: Relevance
“…Our data indicate that, in addition to BCR/CD40 signaling, IL-21 signaling profoundly induces the activation of mTORC1 and c-Myc pathways. This is consistent with a recent report showing that IL-21R signaling is reprogrammed in B GC cells and, compared with BCR/CD40 combination signals, IL-21R signals in synergy with CD40 signals induce distinct differentiation characteristics in B GC cells ( 63 ). Recent reports also showed that IL-21 supports the formation of GCs at an early stage by promoting B GC cell proliferation ( 64 , 65 ) and ASC differentiation even in the absence of cognate help ( 66 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our data indicate that, in addition to BCR/CD40 signaling, IL-21 signaling profoundly induces the activation of mTORC1 and c-Myc pathways. This is consistent with a recent report showing that IL-21R signaling is reprogrammed in B GC cells and, compared with BCR/CD40 combination signals, IL-21R signals in synergy with CD40 signals induce distinct differentiation characteristics in B GC cells ( 63 ). Recent reports also showed that IL-21 supports the formation of GCs at an early stage by promoting B GC cell proliferation ( 64 , 65 ) and ASC differentiation even in the absence of cognate help ( 66 ).…”
Section: Discussionsupporting
confidence: 93%
“…1, G and H). Previous studies demonstrated that interleukin-21 (IL-21) can increase Myc expression in vitro, suggesting a synergistic effect in selection program induction between contact-derived and paracrine signaling ( 38 , 39 ). We were able to repeat these data in vitro, yet injection of recombinant IL-21 into mice did not yield a similar outcome at the protein and RNA level in our experimental settings (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our data suggested that IL-4 signaling may differentially impact B cells at different stages of differentiation during an immune response. To test this hypothesis directly, we isolated naive splenic B cells from naive mice or GL7 + splenic B cells from mice at least 12 days post- Plasmodium infection and cultured them with an agonistic anti-CD40 antibody (1 ug/mL) to promote in vitro GC B cell survival 37,38 . Both cell types were cultured in the presence or absence of non-complexed recombinant IL-4 (10 ng/mL) for 24 hours.…”
Section: Resultsmentioning
confidence: 99%